2017
DOI: 10.1126/science.aal3919
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate colloidal crystals

Abstract: DNA-programmable assembly has been used to deliberately synthesize hundreds of different colloidal crystals spanning dozens of symmetries, but the complexity of the achieved structures has so far been limited to small unit cells. We assembled DNA-modified triangular bipyramids (~250-nanometer long edge, 177-nanometer short edge) into clathrate architectures. Electron microscopy images revealed that at least three different structures form as large single-domain architectures or as multidomain materials. Ordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
186
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(188 citation statements)
references
References 39 publications
2
186
0
Order By: Relevance
“…The diversity of structures and presumably the properties of these materials could be greatly enhanced via postsynthetic modifications, which could be used to generate assemblies in which the constituent NPs are ordered yet separated by relatively large distances-that is, non-closepacked (NCP) NP arrays. Although several examples of related materials have been reported, they are limited to highly specific systems, such as those involving highly directional interactions (13,14) or a fine balance between attractive and repulsive forces during self-assembly (15). Thus, a general route to NCP NP arrays has been lacking.…”
mentioning
confidence: 99%
“…The diversity of structures and presumably the properties of these materials could be greatly enhanced via postsynthetic modifications, which could be used to generate assemblies in which the constituent NPs are ordered yet separated by relatively large distances-that is, non-closepacked (NCP) NP arrays. Although several examples of related materials have been reported, they are limited to highly specific systems, such as those involving highly directional interactions (13,14) or a fine balance between attractive and repulsive forces during self-assembly (15). Thus, a general route to NCP NP arrays has been lacking.…”
mentioning
confidence: 99%
“…Recently reported assembly of bipyramid NCs Ref. [41] into FK phases suggests that disclination networks and icosahedral order is a general tendency for single component systems with different geometrical shapes, a topic that will need to be analyzed in further studies.…”
mentioning
confidence: 99%
“…Inspired by clathrates from molecular and atomic scale, Lin et al reported a huge and complex building block: a triangular bipyramid with long edge ≈250 nm and short edge ≈ 177 nm. DNA shells containing more than 200 duplex functionalized on the surface could guide these building blocks to assemble into clathrate colloidal crystals with domains larger than 10 µm …”
Section: Toward “Atypical” Inorganic Coresmentioning
confidence: 99%
“…This strategy opens a new gate for assembly of nanoparticles with different size, symmetry, and component by programming DNA hybridizations with more accurate control. Afterward, we are going to describe case by case how scientists in this field extended the library of cores from SGN to anisotropic ones, and to other inorganic nanoparticles with properties including magnetism, catalysis, fluorescence, and so on. In 2016, Tian et al proposed a new series of cores‐framed DNA polyhedra, which were folded by DNA origami technology.…”
Section: Introductionmentioning
confidence: 99%